Clinical features and treatment status of adult myasthenia gravis in Japan. Issue 1 (4th February 2014) - Murai, Hiroyuki; Masuda, Masayuki; Utsugisawa, Kimiaki; Nagane, Yuriko; Suzuki, Shigeaki; Imai, Tomihiro; Motomura, Masakatsu; Konno, Shingo; Kira, Jun‐ichi
Abstract Objective Myasthenia gravis (MG) is classified as early‐onset MG (EOMG; age at onset ≤49 years), late‐onset MG (LOMG; age at onset ≥50 years) or thymoma‐associated MG (TAMG) (E‐L‐T classification). To clarify the characteristics of each group in the E‐L‐T classification in Japan, we carried out multicenter analyses of MG. Methods A total of 640 adult patients from 11 MG centers participated in the study. Age at onset, sex, clinical symptoms, frequency of crisis, thymic pathology, positivity of autoantibodies against acetylcholine receptor (AChR) and muscle‐specific receptor tyrosine kinase (MuSK), selected treatment, Cushingoid appearance and post‐intervention status were evaluated in each group. Results EOMG, LOMG and TAMG accounted for 44%, 33%, and 23% of the patients, respectively. Females predominated in the EOMG group (77%), whereas there was no sex difference in the LOMG group. The frequency of ocular MG was the highest in the LOMG group (EOMG 15%, LOMG 38%, TAMG 12%). Bulbar symptoms and crisis were most frequent in the TAMG group. Anti‐AChR antibody was always positive in patients with TAMG (EOMG 70%, LOMG 78%, TAMG 99%), whereas anti‐MuSK antibody was never positive in TAMG patients, and more frequently detected in EOMG patients than in LOMG patients. Thymectomy was carried out in 51% of EOMG patients, 26% of LOMG patients and 97% of TAMG patients. Immunotherapy was carried out most aggressively in TAMG patients, and least aggressively in LOMG patients. Minimal manifestations or better with prednisolone ≤5 mg were achieved only in one‐third of EOMG and TAMG patients. Conclusion Thymoma‐associated MG required the most aggressive immunotherapy, followed by early‐onset MG.